(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdfcGM Hbhdg (B: (3GdfcGM ai GddZg GdVe hGdLeY hONhd GdTF ai GdTF s
(3BNQgG (B:s
(3jfJgi GdehLhO efg CKfGA GdcdGe Yf GdJQgjH fe GdEeYGf ai GdTHY hGdJhSY ai GdeCcd hGdeTGQH Hbhdg (B: (3Ke NaV QCSg ahVY jOg Ydi LHgJg abGd SHMGf Gddg SHMGf Gddg eG CfRd ef GdJTOjO GdMOjK s
(3GdfSNI HgG MhGTs
(3HgG HYV GdhQbGJ cJHJ HNW eZGjQ hHgG HjGV bdjds
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs